THE EFFECT OF THE USE OF BIRTH BALL ON PROGRESS OF LABOR WHEN I PHASE ACTIVE ON PRIMIPARA - ika putri ramadhani (HUMAN CARE JOURNAL, 2022)
Long labor is a contributor to maternal mortality in the world, based on the WHO in 2018, cases of prolonged labor were 289 per 100,000 live births. Birthball is a physical therapy ball to help the process of labor progress.The purpose of this study was to determine the effect of the effectiveness of using Birth Ball on the Progress of Childbirth during the Active Phase I in Primiparas at the Independent Practice of Midwife Ika Putri Ramadhani, M. Bioemd Tahun 2022. The research design was a pre-experimental static Group Comparison design. Statistical test with Independent T Test. The population of this study were primiparous mothers. The sample is 32 people. The results of the study on the use of birthballs showed that the average progress of labor was 288 minutes. The results of the statistical test, the significance value of 0.00, which means p <0.05, it can be concluded that there is a difference in the effectiveness of the use of birthball on the progress of labor in the active phase of the first stage in primiparas. The conclusion of this study is that the use of birth balls can affect the progress of labor and relaxation murottalal-qur'an music therapy can not affect the progress of the active phase of the first stage of labor. advice for health workers As input and consideration in the Midwife's Independent Practice in making plans to improve maternal care during childbirth. For Researchers Increase knowledge, skills and experience in the research process regarding the effect of using birthballs on the progress of the active phase of labor and being able to apply the knowledge that has been gained during education. For further researchers As a reference for further researchers and as a reference for midwives who assist in childbirth.Keywords: BirthBall, and Childbirth Progress